Preliminary assessment of pathogenicity of Fusarium circinatum on germlings of Pinus sylvestris in Ukraine - Davydenko, K. V. (Forestry and Forest Melioration, 2019)
Introduction Conifers are an important component of Ukrainian forest ecosystems. Fusarium circinatum Nirenberg & O'Donnell is one of the invasive pathogens for conifers that have recently been introduced in Europe. It causes pine pitch canker (PPC) and may pose a serious threat to the ecological and economic sustainability of the forest ecosystem. Generally, up to 60 conifers have been reported to be vulnerable to the PPC. The disease is only established in the Iberian Peninsula, but other European countries including Ukraine are also at the risk of infection. The aim of the research was to broaden the knowledge about a new potential invasive disease of pine species, as well as to test the pathogenicity of F. circinatum using germlings of Pinus sylvestris. Material and Methods All tests were carried out at the Research Centre of Quarantine, Invasive and Genetically Modified Organisms, Institute of Plant Protection – NRI (Poznan, Poland) using in vitro virulence test. For this, stratified seeds of P. sylvestris from Ukrainian ecological provenances were soaked and germinated on moistened, sterile filter paper within sterile Petri dishes and incubated at about 22°C. Fifteen-day pine seedlings were amended with a piece of fungal inoculums of Fusarium circinatum. Production of disease symptoms (root rot, damping-off, and no disease, respectively) was monitored and evaluated daily over 28 days. All seedlings were assessed for height growth, root parameters and dry weight as well as were checked for presence/absence F. circinatum using molecular methods and species specific primers. Survival analysis based on the nonparametric Kaplan–Meier estimator was performed with the “Survival” package to test the probability of mortality up to the end of the experiment. Results The obtained results showed that the growth of pine germlings inoculated with Fusarium circinatum varied considerably, but in 28 days F. circinatum in this assay killed all the pine germlings. During the observation period, all inoculated germlings formed long necrotic lesions (8.4–8.7 mm) and showed typical symptoms as basal needle dieback and wilting. Moreover, F. circinatum strongly affected plant development, and the root growth resulted in 92.5–96.7 % of mortality on the 28th day. Previous studies done in Europe, US and Asia have reported considerable differences between susceptibility of different pine species to F. circinatum indicating high or moderate level of virulence and aggressiveness of F. circinatum for seedlings and older plants. Our results are too preliminary; however, our study demonstrated that F. circinatum, if appeared in Ukraine, may become an important pathogen of P. sylvestris in nurseries within a short period. Moreover, the pine shoot beetle (Tomicus piniperda) and other bark beetles were indicated as potential vectors of the pathogen during maturation, feeding on the shoots of healthy pine trees. Since T. piniperda is one of the most common bark beetles in Ukraine, it will be able to increase the potential threat of the diseases pathogen spread within the country. Conclusions The results of the study indicate that Fusarium circinatum may become in future the most important pathogen causing damping-off of Ukrainian pine seedlings, and may pose a serious threat to the Ukrainian forestry in case it is introduced to the country. 2 Figs., 1 Table, 17 Refs.